Psychometric Test of the Indonesian Version of the Procrastination at Work Scale (PAWS) Instrument - Wijaya, Elizabeth; Tondok, Marselius Sampe (Universitas Negeri Malang, 2024)
The Procrastination at Work Scale (PAWS) is an instrument that can be used to measure the level of procrastination that occurs in employees. Procrastination can make employees slow in completing assigned tasks. This research aims to obtain a standardized PAWS to be used in Indonesia. PAWS consists of two dimensions, namely soldiering and cyberslacking, and has a total of 12 items. PAWS was analyzed using the confirmatory factor analysis (CFA) method. The analysis results found that PAWS is an instrument with good validity and reliability values. The items contained in it can also measure the workplace procrastination level. However, PAWS is suggested to be a unidimensional instrument.